Poisoned planet : pollution in our world - Greeley, August (New York : PowerKids Press, 2003)
Describes the different types of pollution and the impact they have on the world's climate, water, land, and air.
Pollution in our world -- Air pollution -- Acid rain -- Water pollution -- Stopping pollution.
Includes bibliographical references (p. 23) and index.
4.9.
4.9
3-6
Keywords: Pollution -- Juvenile literature; Pollution; Pollution